Energy Security and Economics of Indian Biofuel Strategy in a Global Context - Herath Gunatilake; David Roland-Holst; Guntur Sugiyarto; Jenn Baka (Asian Development Bank (ADB), 2011)
The emergence of biofuel as a renewable energy source offers opportunities for climate change mitigation and greater energy security for many countries. At the same time, biofuel represents the possibility of substitution between energy and food. For developing countries like India, which imports over 75% of its crude oil, fossil fuels pose two risks - global warming pollution and negative economic impacts of oil price hikes. This paper examines India's options for managing energy price risk in three ways: biofuel development, energy efficiency promotion, and food productivity improvements. The overall results suggest that biodiesel shows promise as a transport fuel substitute that can be produced in ways that fully utilize marginal agricultural resources and hence promote rural livelihoods. First-generation bioethanol, by contrast, appears to have a limited ability to offset the impacts of oil price hikes. Combining the biodiesel expansion policy with energy efficiency improvements and food productivity increases proved to be a more effective strategy to enhance both energy and food security, help mitigate climate change, and cushion the economy against oil price shocks.
hdl:11540/2015
Keywords: 330; Ölpreis; Energieversorgung; Biokraftstoff; Förderung erneuerbarer Energien; Agrarproduktion; Indien